Analysis of the implementation of the Kangaroo Method in a tertiary maternity hospital in Recife, Brazil - Joice Luiza Alves Cândido; Paulo Germano de Frias; Silvia Wanick Sarinho (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To analyze the implementation of the Kangaroo Method in a tertiary maternity hospital in the city of Recife. Method: Evaluative research analyzing the implementation of the 2nd and 3rd stages of the Kangaroo Method. Conducted between November 2021 and May 2022. A logical model of the Kangaroo Method and the respective matrix of indicators were developed, validated by the Delphi technique, referring to the structure, process, definers of the degree of implementation (implemented/partially implemented/incipient), and the outcomes. Professionals from the Kangaroo Unit (n=9), discharge clinic (n=2), basic health units (n=15), municipal manager (n=1) and parents (n=18) were interviewed; medical records were checked along with direct observation. Plausibility relations were established using a deductive approach based on the logical model to compare the degree of implementation of the Kangaroo Method with its outcomes. Results: The 2nd stage was partially implemented (79.2%), as was its integration with the 3rd stage (78.0%). The implementation of the 3rd stage was incipient (58.4%). The mothers adhered to the recommended care and a strengthened bond with their babies (100%). The children were followed up at the discharge clinic (100%), but only 38.8% are in primary health care. Professionals were trained in the maternity ward (90%) and in primary care (37.5%). Conclusion: The Kangaroo Method was partially implemented, showing greater fragility in follow-up after hospital discharge.